2008
DOI: 10.1038/gt.2008.154
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus serotype 35 vector-mediated transduction following direct administration into organs of nonhuman primates

Abstract: Adenovirus (Ad) serotype 35 (Ad35) vectors have attracted remarkable attention as alternatives to conventional Ad serotype 5 (Ad5) vectors. In a previous study, we showed that intravenously administered Ad35 vectors exhibited a safer profile than Ad5 vectors in cynomolgus monkeys, which ubiquitously express CD46, an Ad35 receptor, in a pattern similar to that in humans. However, the Ad35 vectors poorly transduced the organs. In this study, we examined the transduction properties of Ad35 vectors after local adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, an Ad35-based malaria vaccine was shown to protect mice from Plasmodium falciparum sporozoites (77) and induced potent T-cell immunity (83). In addition, Ad35 vectors injected into tissues of nonhuman primates gave rise to specific gene expression at sites of injection in most organs, indicating the high versatility of Ad35 (86,87).…”
mentioning
confidence: 99%
“…For example, an Ad35-based malaria vaccine was shown to protect mice from Plasmodium falciparum sporozoites (77) and induced potent T-cell immunity (83). In addition, Ad35 vectors injected into tissues of nonhuman primates gave rise to specific gene expression at sites of injection in most organs, indicating the high versatility of Ad35 (86,87).…”
mentioning
confidence: 99%
“…As summarized in Table 5, following intramuscular or intravenous delivery, rAAV or recombinant adenoviral vector was detected in serum or blood within several days and in peripheral blood mononuclear cells up to 10 months at levels significantly exceeding the minimal amounts detectable by the assays developed in our study. [15][16][17][18][19] Comparing performance parameters of assays 1, 2 and 3 with data from gene therapy clinical trials and animal studies for which details of a method for vectors detection and results on vector persistence are available ( Table 5), we concluded that direct detection of gene doping through gene transfer using the approach developed and tested in this project is feasible. As evidenced from the referenced papers, viral and nonviral vectors could be detected in blood components days, weeks and sometimes even months after vector transfer using PCR methods whose sensitivity was similar or lower (between several or hundred(s) times) than that of assays 1, 2 and 3.…”
Section: Discussionmentioning
confidence: 93%
“…This indicates that these serotypes could be potentially used to evade preexisting immunity. Vectors have been developed from multiple HAdV serotypes with lower seroprevalence than HAdV-5: HAdV-11 (Holterman et al, 2004;Stone et al, 2005;Abbink et al, 2007), HAdV-35 (Gao et al, 2003;Sakurai et al, 2003Sakurai et al, , 2009Seshidhar Reddy et al, 2003;Vogels et al, 2003;Barouch et al, 2004;Wu and Tikoo, 2004;Abbink et al, 2007;Brouwer et al, 2007;Sakurai, 2008;McVey et al, 2010;Geisbert et al, 2011), HAdV-49 (Lemckert et al, 2006;Abbink et al, 2007), HAdV-26, -48, and -50 (Abbink et al, 2007;Geisbert et al, 2011), HAdV-7 (Nan et al, 2003), and HAdV-6 (Capone et al, 2006). However, since the presence of NAbs depends on AdV exposure, which is closely related to geographical location, seroprevalence studies in different specific populations are very important.…”
Section: Implications Of Antiviral Immune Responses Against Hadv Vectmentioning
confidence: 98%